Voltage-gated sodium channels in diabetic sensory neuropathy: Function, modulation, and therapeutic potential - Bigsby, Stephanie; Neapetung, Joseph; Campanucci, Verónica A. (Frontiers in Cellular Neuroscience, 2022)
Voltage-gated sodium channels (NaV) are the main contributors to action potential generation and essential players in establishing neuronal excitability. NaV channels have been widely studied in pain pathologies, including those that develop during diabetes. Diabetic sensory neuropathy (DSN) is one of the most common complications of the disease. DSN is the result of sensory nerve damage by the hyperglycemic state, resulting in a number of debilitating symptoms that have a significant negative impact in the quality of life of diabetic patients. Among those symptoms are tingling and numbness of hands and feet, as well as exacerbated pain responses to noxious and non-noxious stimuli. DSN is also a major contributor to the development of diabetic foot, which may lead to lower limb amputations in long-term diabetic patients. Unfortunately, current treatments fail to reverse or successfully manage DSN. In the current review we provide an updated report on NaV channels including structure/function and contribution to DSN. Furthermore, we summarize current research on the therapeutic potential of targeting NaV channels in pain pathologies, including DSN.